Answer:
x = 9
y = -3
Step-by-step explanation:
i will solve this equation simultaneously using the substitution method
so let
3x + 4y = 15..................................... equation 1
3x - y = 30...................................... equation 2
from equation 2
3x - y = 30...................................... equation 2
y = 3x -30..................................... equation 3
substitute for the value of y in equation 1
3x + 4y = 15..................................... equation 1
3x + 4( 3x -30)= 15
3x + 12x- 120 = 15
15x - 120 = 15
15x = 15 + 120
15x = 135
divide both sides by 15 which is the coefficient of x
15x/15 = 135/ 15
x = 9
put the value of x in equation 3
y = 3x -30..................................... equation 3
y = 3(9) - 30
y = 27 - 30
y = -3